2011
DOI: 10.1186/1471-2407-11-66
|View full text |Cite
|
Sign up to set email alerts
|

Identification of epigenetically regulated genes that predict patient outcome in neuroblastoma

Abstract: BackgroundEpigenetic mechanisms such as DNA methylation and histone modifications are important regulators of gene expression and are frequently involved in silencing tumor suppressor genes.MethodsIn order to identify genes that are epigenetically regulated in neuroblastoma tumors, we treated four neuroblastoma cell lines with the demethylating agent 5-Aza-2'-deoxycytidine (5-Aza-dC) either separately or in conjunction with the histone deacetylase inhibitor trichostatin A (TSA). Expression was analyzed using w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 40 publications
3
74
0
Order By: Relevance
“…However, only four publications perform a genome-wide expression study after a pharmacologic unmasking screening strategy. 28,31,32,34 In all four publications, this led to the discovery of previously undescribed DNA-methylation biomarkers in NB. In all other research papers, re-activation is shown by (quantitative) PCR for a limited set of genes of interest, in order to demonstrate the link between DNA-methylation and transcriptional silencing in NB cell lines.…”
Section: Candidate Gene Case Study: Apoptosis and Methylation In Neurmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only four publications perform a genome-wide expression study after a pharmacologic unmasking screening strategy. 28,31,32,34 In all four publications, this led to the discovery of previously undescribed DNA-methylation biomarkers in NB. In all other research papers, re-activation is shown by (quantitative) PCR for a limited set of genes of interest, in order to demonstrate the link between DNA-methylation and transcriptional silencing in NB cell lines.…”
Section: Candidate Gene Case Study: Apoptosis and Methylation In Neurmentioning
confidence: 99%
“…A frequently used high-throughput platform, making use of different probe types for methylated vs. unmethylated bisulfite treated DNA is the Illumina Infinium HumanMethylation27 BeadChip. This technique with over 27,000 methylation-specific probes has recently been applied on NB primary samples 34 and has led to the identification of several novel methylation biomarkers that show potential for prognostic use.…”
Section: Epigenetics and Neuroblastoma Prognosismentioning
confidence: 99%
“…Structural integrity and coordinated biosynthesis of the two chains are critically important for tissue morphogenesis, growth, homeostasis, and repair [11]. Hypermethylation of COL1A2 has been described in many cancers, mainly adenocarcinomas, including colorectal cancer [12], melanoma [13], bladder cancer [14], neuroblastoma [15], medulloblastoma [16,17], breast cancer [18], and hepatoma [19]. The investigation for oncogenic mechanism by COL1A2 gene inactivation was also recently progressing.…”
Section: Introductionmentioning
confidence: 99%
“…The dusp23 gene is highly methylated and decreased dusp23 mRNA expression is observed in neuroblastoma [107]. Interestingly, dusp23 mRNA levels were lower in tumors from deceased patients than patients exhibiting no clinical symptoms, suggesting that DUSP23 levels could be a prognostic marker for neuroblastomas [107].…”
Section: Dusp23mentioning
confidence: 93%
“…Interestingly, dusp23 mRNA levels were lower in tumors from deceased patients than patients exhibiting no clinical symptoms, suggesting that DUSP23 levels could be a prognostic marker for neuroblastomas [107]. The generality of dusp23 functioning as a tumor suppressor is called into question by observations that it is amplified in many other cancers, including breast, colon, lung, squamous carcinoma, pancreatic, brain, esophageal, stomach, bladder, kidney, skin, ovary, prostate, and testicular cancers [108], and selective over-expression of dusp23 in MCF7 cells increased proliferation while knock-down of dusp23 decreased proliferation [108].…”
Section: Dusp23mentioning
confidence: 99%